Effect of Ethrel as a Flower Induction Agent on the Growth and Quality of Fresh Golden Pineapple (MD2) in Malaysia - Sahil Mohedin Hawa; wan sieng yeo; Tze Khiun Jong; Alex Choon Teck Jong; Agus Saptoro; Shiew Wei Lau (Journal of Applied Science & Process Engineering, 2023)
Ethrel was proposed as a good flowering agent to induce the flowering of various fresh pineapples. However, very limited research studies have been carried out on the effect of this inducing agent on the growth of the golden pineapple or Millie Dillard (MD2) in Malaysia, with none in Sarawak. To address this research gap, this study aims to investigate the effect of ethrel on the growth and fruit quality of MD2 pineapples growth in Miri, Sarawak. In this study, ethrel acts as an induction agent that was applied to induce the pineapples at maturity around 11 months after planting (MAP). Moreover, these induced pineapples were harvested 15 MAPs, whereas no pineapples were available for harvesting from the control group that was induced by natural flowering. These results showed that ethrel provided a higher yield in the number of pineapples compared to natural flowering, classifying them as Grade B pineapples. For the growth and fruit quality of the MD2 pineapples, it was found that the average values for the total soluble solids (TSS), total titratable acidity (TTA), pH, diameter, height with a crown, and whole fruit fresh weights with the crown of the pineapples were 16.48 Brix, 0.54 %, pH 3.89, 11.7 cm, 40.3 cm, and 1.4 kg, respectively. Furthermore, the average TSS to TTA ratio was 32.52, which was within the range of 5.5 to 66.4, indicating that the pineapples were sweet with prospects for commercial selling. Hence, it can be concluded that using ethrel as an induction agent is significant in Malaysia.